PENGEMBANGAN BISNIS PARIWISATA MELALUI INOVASI PRODUK DAN PENATAAN MANAJEMEN PADA PASAR WISATA PANDESARI - Desi Anggarwati; Yusuf Purwanto; Agung Winarno; Agus Hermawan (Rafandha Press, 2023)
The development of a tourist village is part of the implementation of tourism that is directly related to services and requires collaboration with the village government and the tourism organizing community. One form of tourism development carried out by Bumdes is the tourism market tourism area in Pandesari Village, Pujon District, Malang Province. Currently, the condition of the Pandesari tourism market has not fully met the requirements as a tourist destination due to its less-than-optimal management. This activity aims to help the Pandesari tourism market regarding the use of digital marketing as a means of developing MSMEs. The community service stage consists of several stages, including1) creating social media, 2) implementing financial management practices, 3) inputting SOP files and cooperation agreements, 4) basic tourism training, 5) designing brochures, banners/posters. The results of the training and mentoring for the tourism market SMEs are: 1. The tourism market SMEs have social media. 2. The tourism market is starting to organize its finances properly 3. The tourism market already has SOP files and cooperation agreements, 4. The tourism market has brochures that are very attractive to visitors.